PENGEMBANGAN SISTEM PENGENDALIAN TRAFFIC DAN WEB FILTERING PADA JARINGAN INTERNET BERBASIS HOTSPOT - Robianto, Riska (LLDIKTI Wilayah X, 2016)
Utilization of Internet services to the hotspot network raises particular problems in traffic control and web filtering. Linux as an operating system that is open (open source), offers a variety of internet firewall systems to assist in the management of traffic, bandwidth, web filtering and one using Smoothwall Express to Linux which can convert a personal computer (PC) to the Internet firewall reliable and stable. Smoothwall allows to integrated with the add-ons extends like AdvProxy and URL Filter to improve the performance of Smoohtwall and simplify configuration of the traffic control and web filtering. The research was conducted by collecting data from various sources related, then experiment with implementing Smoohtwall by adding add-ons extends to help administrators manage and regulate the bandwidth allocation of each client, block websites (URLs) that are not needed. Based on these results bandwidth management can be divided equally and can block websites (URLs) that are not needed like porn sites, warez, bad word, and also the quality of the network connection updatesites more stable.